Adolescents and young adult acute myeloid leukemia outcomes at pediatric versus adult centers: A population‐based study. Issue 8 (8th February 2021) - Gupta, Sumit; Baxter, Nancy N.; Sutradhar, Rinku; Pole, Jason D.; Nagamuthu, Chenthila; Lau, Cindy; Nathan, Paul C.
Abstract: Background: Adolescents and young adult (AYA) acute myeloid leukemia (AML) outcomes remain poor. The impact of locus of care (LOC; adult vs pediatric) in this population is unknown. Procedure: The IMPACT cohort comprises detailed data for all Ontario, Canada, AYA aged 15‐21 years diagnosed with AML between 1992 and 2012, linked to population‐based health administrative data. We determined the impact of LOC on event‐free survival (EFS) and overall survival (OS), treatment‐related mortality (TRM), and relapse/progression. Results: Among 140 AYA, 51 (36.4%) received therapy at pediatric centers. The five‐year EFS and OS for the whole cohort were 35.0% ± 4.0% and 53.6% ± 4.2%. Cumulative doses of anthracycline were higher among pediatric center AYA [median 355 mg/m 2, interquartile range (IQR) 135‐492 vs 202 mg/m 2, IQR 140‐364; P = 0.003]. In multivariable analyses, LOC was not predictive of either EFS [adult vs pediatric center hazard ratio (HR) 1.3, 95% confidence interval (CI) 0.8‐2.2, P = 0.27] or OS (HR 1.0, CI 0.6‐1.6, P = 0.97). However, patterns of treatment failure varied; higher two‐year incidence of TRM in pediatric centers (23.5% ± 6.0% vs.10.1% ± 3.2%; P = 0.046) was balanced by lower five‐year incidence of relapse/progression (33.3% ± 6.7% vs 56.2% ± 5.3%; P = 0.002). Conclusions: AYA AML survival outcomes did not vary between pediatric and adult settings. Causes of treatment failure were different, with higher intensity pediatric protocols associated with higher TRM but lower relapse/progression. Careful risk stratification and enhanced supportive care may be of substantial benefit to AYA with AML by allocating maximal treatment intensity to patients who most benefit while minimizing the risk of TRM.